Proximal RUMM block in dogs: preliminary results of cadaveric and clinical studies. (May 2019) - Tayari, Hamaseh; Otero, Pablo; Rossetti, Alberto; Breghi, Gloria; Briganti, Angela
Abstract: Objective: To design and assess the perioperative analgesic efficacy of an ultrasound (US)-guided radial (R), ulnar (U), median (M) and musculocutaneous (Mc) nerve blocks, performed together in the axillary space by a single, in-plane approach. Study design: Anatomical research and prospective clinical study. Animals: A group of three dog cadavers and 15 client-owned dogs undergoing orthopaedic thoracic limb surgery. Methods: Phase 1: Anatomical dissection and US study of the axillary space were performed to design the US-guided proximal RUMM block. The technique was considered successful if a total volume of 0.15 mL kg –1 new methylene blue solution completely stained the four nerves in two cadavers for ≥2 cm. Phase 2: In 15 client-owned dogs undergoing orthopaedic thoracic limb surgery, the RUMM block designed in phase 1 was performed to provide analgesia using a total volume of 0.15 mL kg –1 of ropivacaine 0.5%. The block was considered effective if the intraoperative fentanyl requirement was <1.2 mcg kg –1 hour –1 and until the postoperative pain score was [short-form Glasgow Composite Measure Pain Scale (SF-GCMPS)] ≤5/20. Results: Phase1: Detection of the four nerves was always feasible in a single US-window. The axillary artery and Mc nerve were used as landmarks. In-plane needling approach was feasible in both cadavers. All the nerves were completely stained for >2 cm. No intrathoracic dye spread was found. Phase 2: In 14/15 anaesthetized dogs, mean intraoperative fentanyl requirement was 0.25 ± 0.05 mcg kg –1 hour –1 . Postoperatively, all dogs had SF-GCMPS ≤5/20 up to 8 hours. Conclusions and clinical relevance: The US-guided proximal RUMM block performed at the axillary level with a single, in-plane needling approach using 0.15 mL kg –1 of ropivacaine 0.5% minimized fentanyl requirement during thoracic limb surgery, contributing to postoperative analgesia up to 8 hours after execution of the peripheral nerve block.